Self-excited primary and secondary instability of laminar separation bubbles - Rodríguez, Daniel; Gennaro, Elmer Mateus; Souza, Leandro F. (Cambridge University Press (CUP), 2020)
The self-excited instabilities acting on laminar separation bubbles in the absence of external forcing are studied by means of linear stability analysis and direct numerical simulation. Previous studies demonstrated the existence of a three-dimensional modal instability, that becomes active for bubbles with peak reversed flow of approximately of the free-stream velocity, well below the required for the absolute instability of Kelvin-Helmholtz waves. Direct numerical simulations are used to describe the nonlinear evolution of the primary instability, which is found to correspond to a supercritical pitchfork bifurcation and results in fully three-dimensional flows with spanwise inhomogeneity of finite amplitude. An extension of the classic weakly non-parallel analysis is then applied to the bifurcated flows, that have a strong dependence on the cross-stream planes and a mild dependence on the streamwise direction. The spanwise distortion of the separated flow induced by the primary instability is found to strongly destabilize the Kelvin-Helmholtz waves, leading to their absolute instability and the appearance of a global oscillator-Type instability. This sequence of instabilities triggers the laminar-Turbulent transition without requiring external disturbances or actuation. The characteristic frequency and streamwise and spanwise wavelengths of the self-excited instability are in good agreement with those reported for low-Turbulence wind-Tunnel experiments without explicit forcing. This indicates that the inherent dynamics described by the self-excited instability can also be relevant when external disturbances are present.
Keywords: absolute/convective instability; boundary layer stability; transition to turbulence